THE MAPPING OF ARABIC LANGUAGE LEARNING IN SENIOR HIGH SCHOOLS AND VOCATIONAL SCHOOLS IN MALANG REGENCY - Mohammad Ahsanuddin; Moh. Ainin; Imam Asrori (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This study aims to map the learning of Arabic in Senior High Schools and Vocational Schools in Malang Regency covering the aspects of 1) teacher qualification, 2) curriculum and development, 3) teaching materials, 4) teaching strategies, 5) instructional media, and 6) evaluation implementation. The research was conducted with a descriptive model. Of the population 183 Senior High School and Vocational Schools, 12 schools were taken using a cluster sampling. The data were collected using questionnaires filled by Arabic teachers in all sample schools. The data analysis was performed according to the steps a) identification of data, b) tabulation of data, c) data grouping, d) data quantification, and e) description of data. This study found (1) all Arabic teachers in Senior High Schools and Vocational Schools in Malang Regency have a standard qualification of Arabic teacher in school, (2) Senior High Schools and Vocational Schools in Malang Regency using the Ministry of Education and Culture KTSP curriculum which was elaborated by teachers into syllabus form and Lesson plans, (3) teaching materials used were in the form of textbooks and student worksheets with various titles and publishers, (4) reading and vocabulary learning was carried out with translation techniques; speaking skills were trained by giving students time to practice dialogue, and writing skills were trained through sentence exercises, copying texts, combining two sentences, and completing paragraphs; (5) teachers utilized instructional media, drawings, original objects, hearing, charts/scheme, or language lab; and (6) the majority of teachers evaluated the lessons at the end of each unit.